2018
DOI: 10.1177/2399808318783206
|View full text |Cite
|
Sign up to set email alerts
|

Emerging urban form – Emerging pollution: Modelling endogenous health and environmental effects of traffic on residential choice

Abstract: Air pollution bears severe health and environmental impacts and is of increasing concern to urban planners but densification strategies have ambiguous impacts. We analyse how households’ aversion to generating and being exposed to traffic pollution at the residential place and during their commute influences emerging urban structures and how these structures in turn affect pollution exposure and the residential choice of households. Resulting spatial patterns are difficult to predict because of this feedback a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…This might result in polycentric urban structures or increased commuting distances if employees consider remote working options or altered office hours. Lastly, increasing the spatial complexity of the model, as for instance done in 2D by Schindler and Caruso (2018), would allow for advanced discussion of neighborhood effects in addition to distance-related effects and policies. For example, they found that setting back houses from main networks or adequately located green space is an effective policy to reduce exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might result in polycentric urban structures or increased commuting distances if employees consider remote working options or altered office hours. Lastly, increasing the spatial complexity of the model, as for instance done in 2D by Schindler and Caruso (2018), would allow for advanced discussion of neighborhood effects in addition to distance-related effects and policies. For example, they found that setting back houses from main networks or adequately located green space is an effective policy to reduce exposure.…”
Section: Discussionmentioning
confidence: 99%
“…If households value local air quality and want to reduce their own exposure to pollution, the intra‐urban distribution of the population will be more dispersed (e.g., Robson 1976; Schindler, Caruso, and Picard 2017). Conversely, the increased environmental consciousness of households (or of policy makers) may lead to further concentration around central locations in order to reduce commuting trips, hence own emissions (e.g., Schindler and Caruso 2018) and their impact on others. It is particularly intriguing for a household that environmental or equity concerns oppose to its health concern and willingness to reduce its own exposure to pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a feedback effect between urban form and pollution. Schindler et al (2017) are the first to model how air quality might impact residential location choice in a linear city; Schindler and Caruso (2018) increased the spatial complexity of urban form to two dimensions. However, transport choices are not modelled as commute by car is assumed to be the only mode of transport (Schindler and Caruso, 2014;Schindler et al, 2017;Schindler and Caruso, 2018;Schindler and Caruso, 2021).…”
Section: Linking Urban Form Transport Planning and Air Quality Modelsmentioning
confidence: 99%
“…When desirable traits scale super-linearly, or undesirable traits scale sub-linearly, the implication for policy-making is that organizing society into larger urban units can deliver improvements with respect to these traits. These scaling relationships prompt explanations in terms of a small set of basic principles that operate locally and describe the intrinsic socio-economic nature of urban living [16], in terms of parsimonious agent-based modeling [15], or via multiple regression model-finding of various kinds, e.g. [19,28].…”
Section: Scaling Characteristics Of Citiesmentioning
confidence: 99%
“…Our study is complementary to recent approaches which seek to simulate the development of canonical urban forms (i.e. dense cities, sprawl, etc) using agent-based approaches [15].…”
Section: Introductionmentioning
confidence: 99%